The Experience of Participation in Suicide Research From the Perspective of Individuals With Bipolar Disorder. Issue 11 (November 2016) - Owen, Rebecca; Gooding, Patricia; Dempsey, Robert; Jones, Steven
Abstract : Abstract: Reasons underlying the elevated prevalence of suicide in bipolar disorder remain underresearched and poorly understood. Participation in suicide-focused research may pose a risk to vulnerable groups, such as those with bipolar disorder. Participants were asked to provide feedback about their experience of participating in a suicide-focused qualitative research interview. The data set was analyzed using inductive thematic analysis. Qualitative themes were (1) talking about suicide was not distressing, (2) negative interview expectations, (3) personal benefits, (4) value of suicide research, (5) interview advice, and (6) talking about suicide was difficult. Suicide-focused research can be conducted with minimal participant distress. Sufficient procedures must be in place, both to identify those at risk of experiencing distress and to efficiently deal with any distress that might occur.